Advances in the Structure of GGGGCC Repeat RNA Sequence and Its Interaction with Small Molecules and Protein Partners - Liu, Xiaole; Zhao, Xinyue; He, Jinhan; Wang, Sishi; Shen, Xinfei; Liu, Qingfeng; Wang, Shenlin (Molecules (Basel, Switzerland), 2023)
The aberrant expansion of GGGGCC hexanucleotide repeats within the first intron of the C9orf72 gene represent the predominant genetic etiology underlying amyotrophic lateral sclerosis (ALS) and frontal temporal dementia (FTD). The transcribed r(GGGGCC)n RNA repeats form RNA foci, which recruit RNA binding proteins and impede their normal cellular functions, ultimately resulting in fatal neurodegenerative disorders. Furthermore, the non-canonical translation of the r(GGGGCC)n sequence can generate dipeptide repeats, which have been postulated as pathological causes. Comprehensive structural analyses of r(GGGGCC)n have unveiled its polymorphic nature, exhibiting the propensity to adopt dimeric, hairpin, or G-quadruplex conformations, all of which possess the capacity to interact with RNA binding proteins. Small molecules capable of binding to r(GGGGCC)n have been discovered and proposed as potential lead compounds for the treatment of ALS and FTD. Some of these molecules function in preventing RNA–protein interactions or impeding the phase transition of r(GGGGCC)n. In this review, we present a comprehensive summary of the recent advancements in the structural characterization of r(GGGGCC)n, its propensity to form RNA foci, and its interactions with small molecules and proteins. Specifically, we emphasize the structural diversity of r(GGGGCC)n and its influence on partner binding. Given the crucial role of r(GGGGCC)n in the pathogenesis of ALS and FTD, the primary objective of this review is to facilitate the development of therapeutic interventions targeting r(GGGGCC)n RNA.